Pemahaman Mahasiswa Ilmu Al-Qur’an dan Tafsir IAIN Sultan Amai Gorontalo Terhadap Kisah Isra>’i>liya>t dalam QS al-Baqarah/2: 67-74 dan QS Yu>suf/12: 24-28 - Ibrahim, Fitrah; Ibrahim, Sulaiman; Asfar, Khaerul (Program Studi Ilmu Al-Quran dan Tafsir, 2023)
The main study of this research aims to know and examine how the story of isra>’i>liya>t in QS al-Baqarah/2: 67-74 and QS Yu>suf/12: 24-28, and how the understanding of students of al-Qur’an Science and Tafsir IAIN Sultan Amai Gorontalo towards the story of isra>’i>liya>t in QS al-Baqarah/2: 67-74 and QS Yu>suf/12: 24-28. This article uses a type of qualitative research, namely field research using the tafsir approach and phenomenological approach using the tahli>li> method (analysis), this method seeks to explain the content of the verses of the Qur’an from various segments, with two data sources, namely primary and secondary data sources. There is also the preparation of the discussion in a perfect framework (outline); and by studying the verses, and analyzing the understanding of students through the results of interviews. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that with the scientific basis possessed by students of al-Qur’an and Tafsir Science, it turns out that not all of them know and understand the stories of isra>’i>liya>t, especially the stories in QS al-Baqarah /2: 67-74 and QS Yu>suf/12: 24-28. Only some of them understand this story, and some of the students of al-Qur’an and Tafsir Science understand it through textual meaning. The description of the results of the interview shows that the students of al-Qur’an and Tafsir need to increase the references in the studies of tafsir, regarding the story in the Qur’an and the meaning of the story based on the understanding of critical analysis of tafsir studies. The implications of this research can be useful as an enhancer of Islamic insight, especially in the field of tafsir and academic development, and is a simple contribution to developing the study of the Qur’an and for the benefit of further studies which are expected to be useful as reference material for further research.